2020
DOI: 10.1038/s43018-020-0096-5
|View full text |Cite
|
Sign up to set email alerts
|

Personalized circulating tumor DNA analysis as a predictive biomarker in solid tumor patients treated with pembrolizumab

Abstract: Immune checkpoint blockade (ICB) provides clinical benefit to a subset of patients with cancer. However, existing biomarkers do not reliably predict treatment response across diverse cancer types. Limited data exist to show how serial circulating tumor DNA (ctDNA) testing may perform as a predictive biomarker in patients receiving ICB. We conducted a prospective phase II clinical trial to assess ctDNA in five distinct cohorts of patients with advanced solid tumors treated with pembrolizumab (NCT02644369). We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
267
3
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 320 publications
(308 citation statements)
references
References 33 publications
6
267
3
2
Order By: Relevance
“…Recently, the first positive results were announced for the Checkmate-743 trial, demonstrating that combining aPD-1 and aCTLA-4 therapy led to improved OS in MPM, as compared to chemotherapy [19] . In contrast, aPD-1 monotherapy failed to improve PFS and OS [9] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the first positive results were announced for the Checkmate-743 trial, demonstrating that combining aPD-1 and aCTLA-4 therapy led to improved OS in MPM, as compared to chemotherapy [19] . In contrast, aPD-1 monotherapy failed to improve PFS and OS [9] .…”
Section: Discussionmentioning
confidence: 99%
“…Phase II trials in MPM also suggest improved clinical responses upon combination ICI treatment, as the MAPS2 trial (nivolumab plus ipilimumab), the NIBIT-MESO trial (durvalumab (aPD-L1) plus tremelimumab (aCTLA-4)) and the INITIATE trial (nivolumab plus ipilimumab) reported better clinical responses upon combination ICI treatment than reported by trials that investigated monotherapy (nivolumab or pembrolizumab) [16] , [17] , [18] . Recently, the first positive results were announced for the Checkmate-743 [19] , a phase III trial that combined aPD-1 (nivolumab) with aCTLA-4 (ipilimumab) treatment in previously untreated MPM patients. These results are very promising, although the magnitude of the benefit is still awaited.…”
Section: Introductionmentioning
confidence: 99%
“…Longitudinal ctDNA analyses are also in the focus of translational research during ICI therapy. In the recently published INSPIRA trial, a prospective phase II study, 94 patients with solid tumors treated with pembrolizumab where included and serial plasma samples were obtained before and during therapy [ 66 ]. Baseline ctDNA concentrations below the mean were correlated with an increased response rate and better outcome in terms of PFS and OS.…”
Section: Main Textmentioning
confidence: 99%
“…In breast cancer (BC), the leading cancer in women worldwide [ 5 ], an increase in circulating tumor cell (CTC) count [ 6 ] and an increase in circulating tumor DNA (ctDNA) concentration have been shown to correlate with disease progression [ 7 , 8 ]. More specifically, in metastatic BC (MBC) patients, a reduction of the apoptotic CTC count by ≥50% (after one completed treatment cycle) correlated with stable disease, while a reduction of apoptotic CTCs ≤ 10% was specific for early disease progression in 74% of the cases [ 9 ].…”
Section: Introductionmentioning
confidence: 99%